Penyeimbangan Beban Trafo Distribusi Berbasis Data Hasil Pendeteksian Phasa Pelanggan Tegangan Rendah - Anang Dasa Novfowan; Dhimas Dhesah Kharisma; Slamet Nurhadi (Politeknik Negeri Malang, 2026)
Load imbalance caused by varied single-phase customer demand can increase neutral current and affect the operational performance of low-voltage distribution systems. This study evaluates a Power Line Carrier (PLC)-based customer-phase identification workflow to support load balancing at the N1223 distribution substation. A field case-study design was used, with phase-current measurements taken at the low-voltage main distribution panel during peak loading and customer phase data verified using a PLC master-slave system. The initial condition (R = 265 A, S = 133 A, and T = 116 A) produced an unbalance index of 36.45% and a neutral current of 141 A. After phase reassignment in Lines B and C, the highest recorded post-balancing unbalance was 5.1%; at 20:00, R = 166 A, S = 185 A, and T = 172 A produced an unbalance index of 4.1%. The post-balancing neutral current was 16.82 A. These findings show that verified customer-phase data provide a traceable basis for selecting rephasing targets. Quantitative neutral-conductor loss estimates are not reported as a main finding because the conductor resistance, length, and cross-sectional area required for independent verification were unavailable.